Capable faults and seismogenic sources: assessing activity and seismogenic behavior for engineering practices. Cases from Central Italy - Maceroni, Deborah; Falcucci, Emanuela; Gori, Stefano; Galadini, Fabrizio; Moro, Marco; Saroli, Michele (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value=""1":2,"2":"An active fault is defined capable (FAC) when, in fact, it is capable of offsetting the ground surface; while a seismogenic source (SS) is a tectonic structure that generates earthquakes and, under certain conditions, displaces the ground when the deep coseismic rupture propagates up to the surface. Therefore, the FACs may be considered as the surficial expression of SSs. The seismic sequences of central Italy in 2009 and 2016-2017 showed the importance to define and locate “in advance” FACs and SSs in any given area. However, the analysis of the scientific literature shows that the conceptual difference between the FAC and the SS is still marked in Italy. This is demonstrated by the availability of two distinct national databases, that deal separately with the FACs (ITHACA) and the SSs (DISS). This article analyses ITHACA and DISS in the 2009 and 2016-2017 seismic sequences epicentral areas and identifies possible conceptual differences and similarities between FAC and SS. It highlights the need of a well-defined methodological approach that can define and map a FAC as a surficial expression of a SS, to which a certain seismogenic and surface faulting potential can be associated."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">An active fault is defined capable (FAC) when, in fact, it is capable of offsetting the ground surface; while a seismogenic source (SS) is a tectonic structure that generates earthquakes and, under certain conditions, displaces the ground when the deep coseismic rupture propagates up to the surface. Therefore, the FACs may be considered as the surficial expression of SSs. The seismic sequences of central Italy in 2009 and 2016-2017 showed the importance to define and locate “in advance” FACs and SSs in any given area. However, the analysis of the scientific literature shows that the conceptual difference between the FAC and the SS is still marked in Italy. This is demonstrated by the availability of two distinct national databases, that deal separately with the FACs (ITHACA) and the SSs (DISS). This article analyses ITHACA and DISS in the 2009 and 2016-2017 seismic sequences epicentral areas and identifies possible conceptual differences and similarities between FAC and SS. It highlights the need of a well-defined methodological approach that can define and map a FAC as a surficial expression of a SS, to which a certain seismogenic and surface faulting potential can be associated.